Effect of Concentrate Supplementation on Whole Sale Cuts and Sensory Properties of Meat from West African Dwarf Goats - Ocheja, J. O.; Apeh, U. J.; Egbunu, G. F.; Faruna, S. S.; Abalaka, E.O.; Amidu, M.; Faruna, J. M. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
Sixteen (16) male West African dwarf goats were allotted into four (4) dietary treatments with four goats per treatment. They were fed a concentrate diet at 0, 100, 200 and 300g/goat/day and Panicum maximum (Guinea grass) at 300, 200, 100 and 0 g for treatments T1, T2, T3and T4 respectively. Water was served ad-libitum. At the end of the feeding period, 3 goats from each treatment were slaughtered, bled and dressed and thereafter the meat used for the evaluation of whole sale cuts and sensory properties. The feeding duration was 90 days and samples of the concentrate diets and Panicum maximum were analyzed for their proximate composition using standard methods. The experimental design was a completely randomized design and data obtained were subjected to Analysis of Variance using SPSS version 20. All the values for wholesale cuts showed significant (P<0.05) differences across the treatments. Values for neck ranged from 3.80 – 4.5 %.  Similarly all the sensory values were significantly (P>0.05) different and values for overall meat quality ranged from 17.45 – 20.57.   It was concluded that Panicum maximum supplemented with a concentrate diet significantly (P<0.05) improved whole sale cuts and sensory properties of meat from West African dwarf goats. Panicum maximum supplemented with concentrate diets were therefore recommended for goat feeding for improved weights of wholesale cuts and sensory properties.